Israel : Report on the Observance of Standards and Codes. (IMF Staff Country Reports; Country Report, 2012)
Israel's Report on Standards and Codes for the financial sector is presented. The authorities take a proactive approach to supervision and correcting incipient problems, and regulations are generally up to date. The assessment of implementation of the Basel Core Principles for Effective Banking Supervision has been conducted in November 2011 within the framework of the Financial Sector Assessment Program Update for Israel. The Bank of Israel and specifically its Banking Supervision Department headed by the Supervisor of Banks is responsible for prudential oversight of banks.